A new species of Pristimantis (Amphibia: Anura: Strabomantidae) from the Río Abiseo National Park, Peru - Lehr, Edgar; Gregory, Cindy; Catenazzi, Alessandro (Zootaxa, 2013)
We describe a new species of Pristimantis from the Río Abiseo National Park in the Andes of northern Peru. Specimens were collected from 2650 to 3000 m elevation. The new species has a snout–vent length of 24.9–34.2 mm (n = 7) in adult females, and 15.3–23.5 mm (n = 29) in adult males. It differs from other species of Pristimantis in having the snout with a broad, slightly upwards curved, fleshy process. The most similar species, P. phoxocephalus has the snout with a vertical fleshy keel, but differs from the new species by being larger (female SVL up to 38.4 mm vs. 34.2 mm), by having prominent dentigerous processes of vomers (minute in the new species), by lacking an inner tarsal fold (present), by lacking heel tubercles (present), and by having the dorsum in life grey, red or brown and the groin with black and orange or yellow mottling, whereas in the new species the dorsum is rusty reddish-brown with lighter blotches or tannish-brown chevrons, and the groin tan with pale brown flecks.